Botanical application: Android-based learning media to enhance interest in learning plant material - Riantina Fitra Aldya; Rio Febrianto Arifendi (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2021)
Balikpapan Botanical Garden School has a very supportive learning environment, especially in studying plant material, but there are still many students who show low interest in learning so that an application in the form of android application to foster student interest in learning related to plants. This research aims to determine the feasibility of the botanical application as the further development of a flash application with the same theme to enhance interest in learning plant material. This research is used Research and Development (R&D) with ADDIE model which includes the analysis, design, development, implementation, and evaluation stage. The data were collected using a questionnaire to measure students’ learning referring to Mitchell's theory with 25 questions. The result showed that the botanical application is feasible to use with a score of 3,86 (feasible) and 4,16 (very feasible) according to media and material experts, and also a score of 4,47 (very feasible) according to the students. It also can enhance interest in learning plant material at the significance level of 0.002 < 0.05 with 46,6% of students reach the high criterion and the other 53,3% reach the moderate criterion of interest. This android-based of botanical application turns out to be able to enhance interest in learning about plant material due to learners' option to choose learning content depending on their interest.